Tai Chi exercise of short duration alters circulating oxylipins in postmenopausal women: a pilot study - Chwan-Li Shen; John W. Newman; Isabel F. Snodgrass; Danielle J. Caruso; Ming-Chien Chyu; Volker Neugebauer; Bruce A. Watkins (Frontiers in Medicine, 2026)
Tai Chi (TC) is a low-impact physical activity known to improve balance, strength, and cognitive health across the lifespan. We previously reported that 8 weeks of TC altered brain connectivity and circulating oxylipins (OxLs) and endocannabinoids/endocannabinoid-like compounds (eCBs) in postmenopausal (PM) women with knee osteoarthritis. This pilot study examined whether a short TC intervention similarly affects inflammatory OxL and eCB in PM women. Participants completed four TC sessions on non-consecutive days over 10 days. Each session included 10 min of warm-up, 45 min of 24-form Yang-style TC (six repetitions at ~7 min per routine), and 5 min of cool-down. Non-fasting plasma collected at baseline and immediately after the fourth session was analyzed for OxL and eCB using targeted metabolomics. Partial least squares discriminant analysis (PLS-DA) assessed pre-to post-intervention differences, and paired t -tests with false discovery rate correction evaluated metabolite changes. Sixteen PM women (58.9 ± 5.2 years; BMI 33.6 ± 5.4 kg/m 2 ) completed the study. Several OxLs demonstrated PLS-DA variable importance in projection scores >1.0. Post-intervention, 1-AG and 12-hydroxyeicosatetraenoic acid (12-HETE) were generally lower, whereas 18-HEPE was higher. TC produced modest effects on eCBs but more pronounced changes in OxLs. Reduced monoacylglycerols may indicate TC-induced mobilization of fatty acids through enzymes involved in 1-AG metabolism, including phospholipase C, diacylglycerol lipase-α, monoglyceride lipase, and potentially fatty acid amide hydrolase.